2020
DOI: 10.1111/all.14450
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylserine induces eosinophil extracellular trap formation and degranulation: Implications in severe asthma

Abstract: Background: Recent evidence demonstrates that activated eosinophils undergo a distinct form of lytic cell death, accompanied by formation of DNA-based eosinophil extracellular trap (EET) and degranulation, enhancing inflammatory immune responses in asthmatic airways. We previously showed that human blood eosinophils undergo degranulation in response to lysophosphatidylserine (LysoPS), an inflammatory lipid mediator, and strongly express P2Y10, a LysoPS receptor. Methods: We evaluated EET, degranulation, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Hwang et al demonstrated that lyosphosphatidylserine is capable of inducing eosinophil degranulation via its action on P2Y 10 receptor [ 102 ]. A subsequent study demonstrated the ability of lysophosphatidylserine to induce eosinophil extracellular trap formation [ 117 ]. Because P2Y 10 is highly expressed during late stage eosinophil differentiation and in eosinophils isolated from severe asthmatics, it offers the possibility of targeting eosinophil degranulation without affecting their survival [ 102 , 117 ].…”
Section: Phospholipases Play a Key Role In Allergiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hwang et al demonstrated that lyosphosphatidylserine is capable of inducing eosinophil degranulation via its action on P2Y 10 receptor [ 102 ]. A subsequent study demonstrated the ability of lysophosphatidylserine to induce eosinophil extracellular trap formation [ 117 ]. Because P2Y 10 is highly expressed during late stage eosinophil differentiation and in eosinophils isolated from severe asthmatics, it offers the possibility of targeting eosinophil degranulation without affecting their survival [ 102 , 117 ].…”
Section: Phospholipases Play a Key Role In Allergiesmentioning
confidence: 99%
“…Human leukocytes were found to differentially express CB 1 and CB 2 receptors as well as MGL [ 251 , 252 , 253 ]. Eosinophils, in particular, were shown to express MGL and CB 2 receptor [ 117 , 251 , 253 ] and were found to migrate towards 2-AG [ 254 , 255 ]. Furthermore, the expression of the CB 2 receptor is increased in eosinophils from symptomatic allergic donors and upregulated following ovalbumin challenge in mice, while CB 1 expression was found to be upregulated in tonsils from allergic rhinitis patients [ 117 , 256 , 257 ].…”
Section: Phospholipase C (Plc) Cleavage Products: Diacylglycerol (Dag) and Inositol 145-trisphosphate (Ip 3 ) And Endomentioning
confidence: 99%
See 1 more Smart Citation
“…14 EETosis is associated with plasma membrane rupture and release of free granules along with histone-retained chromatin structure that is eosinophil extracellular traps (EETs). 9,15,16 EETs are considered an innate immune system to prevent dissemination of pathogens, but their excess formation could be pathogenic. EETs form stable aggregates that contribute to the viscosity of secretions observed in eosinophilic CRS, 15 eosinophilic otitis media 17 and ABPA.…”
Section: Per S Pec Tive From Eos Inophil B I O Lo Gymentioning
confidence: 99%
“…In inflamed tissue and lumen, eosinophils may undergo an active nonapoptotic cell death termed eosinophil ETosis (EETosis) 14 . EETosis is associated with plasma membrane rupture and release of free granules along with histone‐retained chromatin structure that is eosinophil extracellular traps (EETs) 9,15,16 . EETs are considered an innate immune system to prevent dissemination of pathogens, but their excess formation could be pathogenic.…”
Section: Perspective From Eosinophil Biologymentioning
confidence: 99%